Optimization of ventilation and its effect on the microclimate of a colombian multispan greenhouse (2012)
In Colombia, greenhouse design optimization has not been a relevant topic and, as a consequence, the ventilation systems of current structures are not optimal, generating inadequate microclimates for the development of horticultural species. At the production level, management of the greenhouse climate is deficient, and this factor is not taken into account as a function of characteristics dependent on greenhouse design that cannot be modified during its lifespan. The aim of the present work was to study the efficiency of modifications applied to the ventilation system of a commercial greenhouse available on the Colombian market. This was accomplished by using numerical simulations through the application of the computational fluid dynamics method. Based on the commercial greenhouse design, two modified models were designed by applying structural modifications and changing the orientation of the fixed open ridges. Simulations with the three greenhouse models were carried out in order to maximize the air renovation rates and improve air movement within the entire greenhouse, striving for the highest degree of climate homogenization. The best greenhouse design was the one with the highest air renovation index, high enough to ensure adequate control of temperature and humidity extremes through natural ventilation. Additionally, this design generated the most homogenous microclimate within the cultivation zone